Isolation and Identification of Flavonoids from Arctium Lappa Stem and Study the Hepato Protective Effect on Acetaminophen Induced Liver Damage - Abd Al Salam Alsamarrai, Zaid; Razooq Al-Samarrai, Rafah; Tawfeeq Alsamarrai, Abdulsalam (International Journal of Psychosocial Rehabilitation, 2020)
The present study investigates the hepatoprotective and antioxidant effects of crude extract of Arctium lappa stem (E-ALS) and isolated total flavonoids (ITF) from the stem, with qualitative and quantitative determination of flavonoids by HPLC. Twenty-four local adult male rabbits were used in this study, which was divided into four groups (6 animals in each group): Control-1 (C1) as the control group, Control-2 (C2): treated with 300 mg/kg paracetamol administered for one week, Group 1 (G1): mg/kg paracetamol administered for one week + orally 250 mg/kg of E-ALS administered daily for 4 weeks, Group 2 (G2): orally 300 mg/kg paracetamol administered for one week + orally 50 mg/kg of ITF administered daily for 4 weeks. The results identified five types of flavonoids for the first time in plant stems (rutin, myricetin, quercetin, apigenin, and kaempferol) with quantified determination for the concentration of each type of flavonoid in E-ALS and also in ITF, which identified the same five flavonoids. The hepatoprotective effect of E-ALS and ITF was observed by monitoring the antioxidant parameters and activity of liver enzymes. The results obtained from this study showed that the levels of glutathione-GSH, glutathione peroxidase-GPX, and glutathione-S-transferase-GST were significantly (P ≤ 0.05) decreased in C2 treated with paracetamol as compared with C1, with significant (P ≤ 0.05) elevation of alanine aminotransferase-ALT activity and nonsignificant effect on aspartate aminotransferase-AST, while the levels of GSH and GPX were significantly (P ≤ 0.05) elevated in G1 and G2 treated with E-ALS and ITF, respectively, as compared with C2, in which the levels of GSH and GPX are less than the levels in C1 and G1. Otherwise the levels of GST, ALT, and AST significantly (P ≤ 0.05) decreased in G1 and G2 as compared with C2. These findings show the hepatoprotective properties of E-ALS and IFT against liver injury induced by paracetamol and also the protective role of the anti-oxidative defense system of flavonoids in the two extracts.